DEPENDENCE OF MILK PRODUCTIVITY OF COWS ON LIVE WEIGHT UNDER THE INFLUENCE OF THE VILOFOSS FEED SUPPLEMENT (International Congress on Economics, Management and Business Studies, 2026)
This article presents the results of a study on the relationship between milk productivity and live weight of Simmental cows under the influence of the Vilofoss mineral feed supplement in the conditions of the Tashkent region. The experiment evaluated the effect of two different doses of Vilofoss (170 g and 220 g per head per day) included in the basic ration on milk yield, milk fat content, milk fat yield, and their dependence on live weight during a 305-day lactation period. Zootechnical, biological, and statistical research methods were applied. Milk fat content was determined using the Gerber method, and protein content was analyzed with a Laktan M-4 device. The results showed that supplementation with 170 g of Vilofoss provided the highest milk yield and milk fat output compared to both the 220 g supplementation and the control group. Cows receiving 170 g of Vilofoss produced on average 19–20% more milk and 22–23% more milk fat than the control group. A tendency toward a slight decrease in milk yield with increasing live weight was observed across all groups. The findings indicate that the optimal dose of Vilofoss for Simmental cows under local climatic and feeding conditions is 170 g per head per day. The inclusion of balanced mineral supplements in the ration significantly improves milk productivity and contributes to the formation of highly productive dairy herds.
Keywords: Simmental cows, Vilofoss, mineral feed supplement, milk productivity, live weight, milk fat content, lactation, dairy cattle breeding, feed efficiency, Uzbekistan conditions.